AN ANALYSIS OF EFL TEACHERS’ BELIEFS ABOUT TEACHING WRITING AND THEIR PRACTICES IN VOCATIONAL SCHOOL - Rovikasari, Mala; Suparno, Suparno; Supri, Slamet (Universitas Muhammadiyah Semarang, 2019)
This research aimed to investigate the EFL teachers’ beliefs about teaching writing and their practices in Vocational School and to reveal problems and solutions in teaching writing. The research design used a case study. The subjects were four writing teachers who have been teaching in Vocational School. The data collecting technique used semi-structured interview, observation, and document analysis. Then, the data were analyzed using Flow Model Analysis. To ensure the credibility of data, it used data triangulation and methodological triangulation. The findings showed that the EFL teachers had positive beliefs which covered the nature of teaching writing and its objectives, teachers’ roles, teaching approaches, and writing assessment. There was a relationship between teachers’ belief and practices in teaching writing. The teachers also concerned about the problems: vocabulary, language use, organization, and students’ motivation in teaching writing.